2012
DOI: 10.1371/journal.pone.0044976
|View full text |Cite
|
Sign up to set email alerts
|

Migrating Giant Honey Bees (Apis dorsata) Congregate Annually at Stopover Site in Thailand

Abstract: Giant honey bees (Apis dorsata) of southern Asia are vital honey producers and pollinators of cultivated crops and wild plants. They are known to migrate seasonally up to 200 km. It has been assumed their migrations occur stepwise, with stops for rest and foraging, but bivouacking bees have rarely been seen by scientists. Here I report discovery of a site in northern Thailand where bivouacs appeared in large congregations during the wet seasons of 2009 and 2010. The bivouac congregation stopover site is a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…However, the genus Apis comprises eight more species, all indigenous to Asia, including two dwarf bees, two giant bees and four cavity-nesting bees (Radloff, Hepburn, & Engel, 2011). Behavioural limitations of the dwarf and giant honeybees, particularly their practice of open-air nesting and seasonal migrations, prevent them from being kept commercially by man (FAO, 1990;Robinson, 2012). In contrast, the honeybee species that naturally nest inside cavities can be kept in man-made hives, enabling the colonies to be manipulated for long periods and also being moved between places for foraging.…”
Section: Introductionmentioning
confidence: 99%
“…However, the genus Apis comprises eight more species, all indigenous to Asia, including two dwarf bees, two giant bees and four cavity-nesting bees (Radloff, Hepburn, & Engel, 2011). Behavioural limitations of the dwarf and giant honeybees, particularly their practice of open-air nesting and seasonal migrations, prevent them from being kept commercially by man (FAO, 1990;Robinson, 2012). In contrast, the honeybee species that naturally nest inside cavities can be kept in man-made hives, enabling the colonies to be manipulated for long periods and also being moved between places for foraging.…”
Section: Introductionmentioning
confidence: 99%
“…The giant honeybee (A. dorsata) was the major pollinator for both species in every site with a sharp increase from the village towards the forest interior. Although A. dorsata was reported to be a vital pollinator for both cultivated crops and wild plants (Robinson, 2012), they usually forage in more abundant flower resources (Punchihewa et al, 1985) and may be a poorer competitor than the other two Apis species (Koeniger and Vorwohl, 1979). Studies showed that our three honey bee species compete for food, with A. florea and A. cerana being the stronger competitors than A. dorsata, and this competition can be avoided by differentiation of foraging (Koeniger & Vorwohl, 1979).…”
Section: Impact Of Human Disturbances On Plant Diversity Pollinator mentioning
confidence: 89%
“…In this case, interspecific competition resulted in reduced fledging rates and breeding density of Gouldian Finches (Brazill-Boast et al 2011. Although differences in competitive strength can result in the exclusion of weaker competitors from high-quality habitat (Kempenaers and Dhondt 1991, Robinson andTerborgh 1995, Martin andEadie 1999), sustained competition for cavity resources appears to be relatively common among cavity-nesters with similar body sizes (e.g., Slagsvold 1975, Meek andRobertson 1994). Competitors for nest cavities employ strategies to reduce the degree of competition or to change the balance of competitive strength through subtle shifts in cavity selection (e.g., Robles and Martin 2013) or early timing of breeding (Wiebe 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Counts of migrating animals are typically collected as hourly or daily counts of the number of individuals migrating past a count site (Farmer et al 2007, Findlay et al 2011, as the number of individuals using a count site during migratory stopover (Francis and Hussell 1998, Robinson 2012, McGowan 2015, or as the number of individuals collected injured or dead following collisions with man-made structures (Loss et al 2014, Beston et al 2015. Population trends extrapolated from counts of migrating individuals have shown general correspondence with breeding surveys Hussell 1998, Farmer et al 2007) and provide an important contribution to the identification of research and management priorities that can lead to the improved assessment and conservation of populations (Machtans andThogmartin 2014, McGowan 2015).…”
Section: Introductionmentioning
confidence: 99%